2010
DOI: 10.1186/1471-2334-10-114
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of risk perceptions and correlates of precautionary behaviour related to human avian influenza during 2006 - 2007 in the Netherlands: results of seven consecutive surveys

Abstract: BackgroundAvian influenza (AI) is a public health challenge because of ongoing spread and pandemic potential. Non-pharmaceutical measures are important to prevent the spread of AI and to contain a pandemic. The effectiveness of such measures is largely dependent on the behaviour of the population. Risk perception is a central element in changing behaviour. This study aimed to investigate perceived vulnerability, severity and precautionary behaviour related to AI in the Netherlands during seven consecutive surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
79
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 38 publications
(63 reference statements)
20
79
1
5
Order By: Relevance
“…This is consistent with one previous study conducted in The Netherlands which found that over 90% of the respondents perceived that avian influenza was a serious disease (mean score = 4.57, scale 1–5) but only 0.7% of them perceived themselves to be highly vulnerable to avian influenza (mean score = 1.69, scale 1–5) [48]. Chinese poultry farmers report more familiarity with poultry disease risk than do urbanites and are more optimistic about avoiding avian influenzas [12, 13].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with one previous study conducted in The Netherlands which found that over 90% of the respondents perceived that avian influenza was a serious disease (mean score = 4.57, scale 1–5) but only 0.7% of them perceived themselves to be highly vulnerable to avian influenza (mean score = 1.69, scale 1–5) [48]. Chinese poultry farmers report more familiarity with poultry disease risk than do urbanites and are more optimistic about avoiding avian influenzas [12, 13].…”
Section: Discussionsupporting
confidence: 92%
“…Young adults (18–29 years) appeared as being the most active in terms of prevention, in contrast to other studies which reported elderly people to be more active in applying preventive measures [5,28,29]. Young adults were 8 times more likely to undertake preventive measures than other age groups.…”
Section: Discussioncontrasting
confidence: 70%
“…One interpretation might be that young adults could have reacted well once they realized that they were more exposed to influenza A (H1N1) than other age groups. The research into behavioural attitudes over an extended period during influenza epidemics shows that people are highly adaptive and that their attitudes evolve over time [4,5]. …”
Section: Discussionmentioning
confidence: 99%
“…We found a strong association between holding a university graduate certificate or having high school education and the probability of reporting a 'high' CCHF perceived risk. Studies have shown that individuals with less formal education are less likely to understand and interpret risk information in a proper manner (13,14). Our findings are consistent with results from a previous study that showed an inverse relationship between the level of education and the risk of CCHF infection (15).…”
Section: Discussionsupporting
confidence: 83%